Effects on leg muscular performance from whole-body vibration exercise: a systematic review - Rehn, B.; Lidström, J.; Skoglund, J.; Lindström, B. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The purpose of this study was to investigate the effects on leg muscular performance from whole-body vibration exercise. Literature search was performed on the databases Pubmed, Cinahl, ISI web of science (Sci-expanded, SSCI) and Embase (Rehab & Physical Med). Rating of 19 relevant studies was performed (14 on long-term exercise and five on short-term exercise) using a score system for the methodological quality. Several randomized-controlled trial studies of high to moderate quality show similar improvements from long-term regimen on muscular performance in the legs after a period of whole-body vibration exercise. As there were few studies on short-term exercise and as they had no control groups, the same convincing improvements regarding muscular performance were not achieved. Preliminarily, there is strong to moderate evidence that long-term whole-body vibration exercise can have positive effects on the leg muscular performance among untrained people and elderly women. There is no clear evidence for effects on muscular performance after short-term vibration stimuli.